Financial Literacy in Bosnia and Herzegovina : Analytical Report - Bagić, Dragan (World Bank, Washington, DC, 2017)
The survey on financial literacy among the citizens of Bosnia and Herzegovina was conducted within a larger project that aims at creating the Action Plan for Consumer Protection in Financial Services. The conclusion about the need for an Action Plan was reached by the representatives of the World Bank, the Federal Ministry of Finance, the Central Bank of Bosnia and Herzegovina, private sector supervisory authorities and non-governmental organizations, based on the World Bank’s 2009-2010 Diagnostic Review in Bosnia and Herzegovina. The financial literacy survey, whose results are presented in this report, aims at establishing the basic situation with respect to financial literacy, serving on the one hand as a preparation for the educational activities plan, and on the other as a basis for measuring the efficiency of activities undertaken. The first section of the study deals with financial literacy and its various aspects. Based on these data, the Financial Literacy Index was derived (a single-dimension composite scale of financial knowledge and capability). Next sections deal with managing everyday financial choices (saving, covering shortages etc.) in the context of general household financial situation. Data collection was based on a random, nation-wide sample of citizens of Bosnia and Herzegovina aged 18 or older (N = 1036).